Knowing about genocide : Armenian suffering and epistemic struggles - Savelsberg, Joachim J., 1951- (University of California Press, 2021)
"How do victim and perpetrator peoples generate conflicting knowledge about genocide? Using a sociology of knowledge approach, Savelsberg answers this question for the Armenian genocide committed in the context of the First World War. Focusing on Armenians and Turks, he examines strategies of silencing, denial, and acknowledgment in everyday interaction, public rituals, law, and politics. Drawing on interviews, ethnographic accounts, documents, and eyewitness testimony, Savelsberg illuminates the social processes that drive dueling versions of history. He reveals counterproductive consequences of denial in an age of human rights hegemony, with implications for populist disinformation campaigns against overwhelming evidence"--